The debate on staff language competences and the use of official languages in the Balearic Islands health system - Ballester Cardell, Maria; Marí Mayans, Isidor (Linguistic Minorities and Society, 2021)
The Spanish Constitution of 1978 and the Statute of Autonomy of the Balearic Islands of 1983 established the official nature of both Spanish and Catalan and entrusted public authorities with guaranteeing the right of citizens to use one or the other on an equal footing. Subsequent to the language legislation of 1986, the legal framework of Catalan has varied depending on the majority party that forms a government. The debate stirred up by these regulations demonstrates the difficulties in ensuring real equality between official languages, when social initiatives cannot translate into sufficient political support and the national political context is hostile. The article explores this debate and discusses recent regulations surrounding the official languages competencies of health system staff, from the direct experience of the authors, as members of two consultative institutions on legal and sociolinguistic matters. Keywords: language rights, official language, language competence, medical communication, health services

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

The Use of Welsh in the Third Sector in Wales - Prys, Cynog (Contemporary Wales, 2010)
This article will examine the use of the Welsh language in the third sector in Wales, by studying the experiences of service users and service providers in the counties of Gwynedd and Carmarthenshire. The third sector provides a wide range of services to the public in Wales, from leisure activities to health care services and advocacy, and acts as an important care and service provider. However, the sector does not come directly under the legislation of the Welsh Language Act of 1993, leaving this important sector outside of the influence of current language legislation. This article discusses the results of recent qualitative research carried out on the use of the Welsh language in the sector, users' attitudes towards the language of service, and the experience of service providers in providing a bilingual service to the public.

Bilingual Workforce Recruitment Pack. Bangor University - Prys, Cynog; Bonner, Elen; Hodges, Rhian (2024)
This practical resource aims to offer advice and guidance to employers seeking to address the challenges of recruiting a bilingual workforce. Specifically, this resource has been targeted at companies and organizations that wish to recruit staff with Welsh language skills. It introduces: 1. A toolkit which includes examples of good practice collected during the research as employers shared effective ways of increasing the linguistic capacity of their workforce through recruitment, and 2. Typology, a means of classifying people into different groups which helps employers to identify and target audiences when conducting a recruitment process. This research study has led to evidence showing that many employers face challenges when recruiting staff with Welsh language skills. Additionally, we found that the challenges of recruiting a workforce with Welsh language skills are more intense in some sectors (e.g. care) or specific specialist areas (e.g. information technology).

Navigating the meso-level bottleneck: Language rights implementation in Welsh healthcare - Prys, Cynog; Hodges, Rhian (Revista de Llengua i Dret / Journal of Language and Law, 2025)
Abstract Language is a key factor in the delivery of effective healthcare, especially in settings where service users speak a minoritised language. In Wales, the Welsh Government has acknowledged the importance of linguistic inclusion through initiatives such as the More than just words strategy, which aims to embed the Welsh language into health and social care services. The introduction of The Welsh Language Standards (No. 7) Regulations in 2018 marked a significant statutory development, placing legal obligations on health boards to provide services in Welsh. Despite these policy-level advancements, the integration of Welsh language services within healthcare remains uneven. Reports have highlighted persistent gaps and inconsistencies in Welsh language service provision, raising concerns about the practical challenges of implementation and its impact on service users. In this paper, we examine the structural and operational barriers encountered by meso-level actors – particularly local health boards – responsible for implementing national language policy in everyday service delivery. Although the analysis is situated in the Welsh context, the paper contributes to a broader understanding of the administrative bottlenecks that can arise when implementing public services in a minoritised language context. It highlights the need to critically examine the institutional dynamics that shape the translation of policy into practice and the implications for minoritised languages such as Welsh. Resum La llengua és un element clau en la prestació d’una atenció sanitària de qualitat, sobretot en contextos en què els usuaris parlen una llengua minoritzada. A Gal·les, el Govern gal·lès ha reconegut la importància de la inclusió lingüística a través d’iniciatives com ara l’estratègia More than just words, que té l’objectiu d’integrar la llengua gal·lesa als serveis de salut i d’assistència social. L’any 2018, la introducció del Reglament núm. 7 sobre la llengua gal·lesa va marcar un avenç normatiu important, ja que va imposar obligacions legals d’oferir serveis en gal·lès als consells de salut. Malgrat aquests avenços a nivell polític, la incorporació de serveis en llengua gal·lesa en l’atenció sanitària continua sent desigual. Alguns informes han posat de manifest l’existència de buits continuats i d’incoherències en la prestació de serveis en gal·lès, cosa que ha suscitat interrogants sobre els reptes pràctics de la seva implementació i l’impacte que té en els usuaris. En aquest article s’analitzen les barreres estructurals i operatives que es troben els agents situats al nivell meso –en concret els consells de salut locals– responsables d’implementar les polítiques lingüístiques nacionals en l’atenció diària. Malgrat que l’anàlisi se situa en el context gal·lès, l’article aporta una visió més àmplia dels colls d’ampolla administratius que poden sorgir a l’hora d’implementar serveis públics en un context de llengües minoritzades. També destaca la necessitat d’analitzar críticament les dinàmiques institucionals que modulen la traducció de les polítiques a la pràctica i les implicacions per a llengües minoritzades com ara el gal·lès. Resumen La lengua es un elemento clave en la prestación de una atención sanitaria de calidad, sobre todo en contextos en que los usuarios hablan una lengua minorizada. En Gales, el Gobierno galés ha reconocido la importancia de la inclusión lingüística a través de iniciativas como la estrategia More than just words, que tiene el objetivo de integrar la lengua galesa en los servicios de salud y de asistencia social. En 2018, la introducción del Reglamento núm. 7 sobre la lengua galesa marcó un avance normativo importante, ya que impuso obligaciones legales de ofrecer servicios en galés en los consejos de salud. A pesar de estos avances a nivel político, la incorporación de servicios en lengua galesa en la atención sanitaria sigue siendo desigual. Algunos informes han puesto de manifiesto la existencia de vacíos continuados e incoherencias en la prestación de servicios en galés, lo que ha suscitado interrogantes sobre los retos prácticos de su implementación y el impacto que tiene en los usuarios. En este artículo se analizan las barreras estructurales y operativas que encuentran los agentes situados al nivel meso –en concreto los consejos de salud locales– responsables de implementar las políticas lingüísticas nacionales en la atención diaria. Aunque el análisis se sitúa en el contexto galés, el artículo aporta una visión más amplia de los cuellos de botella administrativos que pueden surgir a la hora de implementar servicios públicos en un contexto de lenguas minorizadas. También destaca la necesidad de analizar críticamente las dinámicas institucionales que modulan la traducción de las políticas a la práctica y las implicaciones para lenguas minorizadas como el galés.

Health providers’ perceptions on language barriers in Catalonia’s public healthcare system - Rubio-Carbonero, Gema; Gil-Bardají, Anna (Revista de Llengua i Dret, 2025)
In this article, we present the results of an exploratory quantitative study on the situation of communication between healthcare staff in the Catalan public system and users with limited competence in the official languages of Catalonia. The study objective is to offer a comprehensive and empirically grounded overview of the current state of intercultural communication in the Catalan public health system, with and without the involvement of third-party mediation, as perceived by healthcare providers. Data were collected through a structured questionnaire administered to professionals engaged in direct patient care across public health centres in Catalonia, yielding a sample of 1 390 respondents. The findings underscore the high frequency and significant impact of language barriers in clinical encounters and highlight notable deficiencies in the resources currently available to address these challenges. , Aquest article presenta els resultats d’un estudi quantitatiu exploratori sobre la situació de la comunicació entre el personal sanitari del sistema públic català i els usuaris que tenen un coneixement limitat de les llengües oficials de Catalunya. L’objectiu de l’estudi és oferir una visió global i amb una base empírica de l’estat actual de la comunicació intercultural en el sistema públic de salut català –tant amb la mediació de tercers com sense– a partir de la percepció que en tenen els professionals sanitaris. Les dades es van recollir mitjançant un qüestionari estructurat administrat a professionals que treballen en l’atenció directa als pacients en centres públics de salut de Catalunya, que va permetre obtenir una mostra de 1.390 participants. Els resultats posen de manifest l’alta freqüència i el fort impacte de les barreres lingüístiques en les interaccions clíniques, així com mancances notables en els recursos disponibles actualment per afrontar aquests reptes. , Este artículo presenta los resultados de un estudio cuantitativo exploratorio sobre la situación de la comunicación entre el personal sanitario del sistema público catalán y los usuarios con un conocimiento limitado de las lenguas oficiales de Cataluña. El objetivo del estudio es ofrecer una visión global y con base empírica del estado actual de la comunicación intercultural en el sistema público de salud catalán –tanto con la mediación de terceros como sin ella– a partir de la percepción de los profesionales sanitarios. Los datos se recogieron mediante un cuestionario estructurado administrado a profesionales que trabajan en la atención directa al paciente en centros públicos de salud de Cataluña, con el que se obtuvo una muestra de 1.390 participantes. Los resultados ponen de manifiesto la elevada frecuencia y el fuerte impacto de las barreras lingüísticas en las interacciones clínicas, así como carencias notables en los recursos disponibles actualmente para afrontar tales desafíos.

Presente, pasado y (sobre todo) futuro de la atención sanitaria en euskera [Present, past and (above all) future of healthcare in Basque] - Zarate Sesma, Jon; Montes, Aitor (Revista de Llengua i Dret, 2025)
Resumen La normalización de la atención sanitaria sería ofrecer una atención integrada basada en la evidencia y centrada en el usuario (paciente), lo que pasa por una atención en el idioma de elección del usuario. Para la consecución de dicha normalización, y teniendo en cuenta la complejidad del sistema sanitario centrado en el usuario, es necesario poner en marcha políticas que apuesten por el impulso de la conciencia lingüística entre los profesionales sanitarios y ofrecer estrategias para asegurar la asistencia sanitaria integral en euskera. Es imprescindible aprobar un nuevo decreto que reemplace el Decreto 67/2003 y que exija como mínimo el nivel C1 en euskera para el ejercicio de la profesión sanitaria. Del mismo modo, habría que registrar el idioma de elección del usuario a través de la oferta activa, impulsar los circuitos sanitarios en euskera (con la identificación de los servicios y profesionales euskaldunes) y poner en marcha la historia clínica en euskera. Resum La normalització de l'atenció sanitària seria oferir una atenció integrada basada en l'evidència i centrada en l'usuari (pacient), la qual cosa passa per una atenció en l'idioma d'elecció de l'usuari. Per a la consecució de l'esmentada normalització, i tenint en compte la complexitat del sistema sanitari centrat en l'usuari, cal posar en marxa polítiques que apostin per l'impuls de la consciència lingüística entre els professionals sanitaris i oferir estratègies per assegurar l'assistència sanitària integral en eusquera. És imprescindible aprovar un nou decret que reemplaci el Decret 67/2003 i que exigeixi com a mínim el nivell C1 d’eusquera per a l'exercici de la professió sanitària. Així mateix, caldria registrar l'idioma d'elecció de l'usuari a través de l'oferta activa, impulsar els circuits sanitaris en eusquera (amb la identificació dels serveis i professionals bascoparlants) i posar en marxa la història clínica en eusquera. Abstract Healthcare normalisation should involve evidence-based and user (patient)-centred integrated care, provided in the user’s language of choice. To achieve this normalisation, and bearing in mind the complexity of the user-centred healthcare system, it is necessary to implement policies that promote language awareness among healthcare professionals and to offer strategies to ensure comprehensive healthcare in Basque. It is essential to pass a new decree to replace Decree 67/2003, requiring a minimum level of C1 in Basque to work as a healthcare professional. The user’s language of choice should also be recorded by the healthcare system, promoting healthcare circuits in Basque (identifying services available in Basque and Basque-speaking professionals) and making medical records available in Basque. Laburpena Osasun-arretaren normalizazioa ebidentzian oinarritutako eta erabiltzailearengan (pazientearengan) zentratutako arreta integratua eskaintzea litzateke, hau da, nahitaez erabiltzailearen aukerako hizkuntzan. Osasun-sistemaren konplexutasunak beharrezkoa egiten du giza kapitalean oinarritutako kultura-aldaketa: hizkuntza-kontzientzia duten langile ekintzaileak. Eztabaida eta paradigma berriak, diskurtso berria, erabiltzailearengan kokatu behar da, eta ez medikuarengan. Etorkizuna, neurri handi batean, osasun-profesionalen artean hizkuntza-kontzientzia sustatzearen aldeko apustua egiten duten politiken mende dago, bai eta osasun-arreta integrala euskaraz bermatzeko estrategiak eskaintzen dituztenen mende ere. Ezinbestekoa da dekretu berri bat onartzea, 67/2003 Dekretua ordeztuko duena eta lanbide sanitarioan jarduteko gutxienez euskarazko C1 maila eskatuko duena. Era berean, erabiltzaileak arretarako aukeratzen duen hizkuntza eskaintza aktiboaren bidez erregistratu beharko litzateke, osasun-zirkuituak euskaraz sustatu beharko lirateke (zerbitzu eta profesional euskaldunak identifikatuta) eta historia klinikoa euskaraz abiarazi beharko litzateke.